2010
DOI: 10.1007/s10479-010-0749-3
|View full text |Cite
|
Sign up to set email alerts
|

Two characterizations of chain partitioned probe graphs

Abstract: Chain graphs are exactly bipartite graphs without induced 2K 2 (a graph with four vertices and two disjoint edges). A graph G = (V , E) with a given independent set S ⊆ V (a set of pairwise non-adjacent vertices) is said to be a chain partitioned probe graph if G can be extended to a chain graph by adding edges between certain vertices in S. In this note we give two characterizations for chain partitioned probe graphs. The first one describes chain partitioned probe graphs by six forbidden subgraphs. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A characterization of chain probe graphs and an O(n 2 ) recognition algorithm was given in Golumbic et al (2009). The partitioned chain probe graph problem assumes that the independent set S is given and fixed in advance, and is a special case of the chain sandwich problem where E 2 \ E 1 = S × S. The complexity of the partitioned chain probe problem has also been shown to be polynomial in Van Bang (2010).…”
Section: Graph Sandwich Problem For Propertymentioning
confidence: 99%
“…A characterization of chain probe graphs and an O(n 2 ) recognition algorithm was given in Golumbic et al (2009). The partitioned chain probe graph problem assumes that the independent set S is given and fixed in advance, and is a special case of the chain sandwich problem where E 2 \ E 1 = S × S. The complexity of the partitioned chain probe problem has also been shown to be polynomial in Van Bang (2010).…”
Section: Graph Sandwich Problem For Propertymentioning
confidence: 99%
“…In case of probe graphs, i.e., k = 1 only few are known: In [1] it is shown that a graph is a partitioned probe threshold graph, respectively, a partitioned probe trivially perfect graph if and only if a certain enhanced graph is a threshold graph, respectively, a trivially perfect graph. In [14] it is shown that a graph is a partitioned chain graph if and only if a certain enhanced graph is a chain graph, and recently, [15] (cf. Theorem 1) proved that a graph is a partitioned block graph if and only if a certain enhanced graph is a block graph.…”
Section: Introductionmentioning
confidence: 99%